Bridging the gap Between Business and Academic Environments. - Madden, Donald L. (The Accounting Review, 1970)
This article presents a discussion of two possible approaches to problems that derive from the apparent gap between business and academic environments. Many firms have taken the initiative in this area, and their Faculty Residency Programs are worthy of much praise. Some faculties have made useful efforts to associate executives with campus programs. In summary, there is little doubt that interested firms can and should obtain benefits from a Faculty Residency Program, either directly through using the faculty member in specialized projects, or indirectly, through the active utilization of his objective attitude in the decision making process. If the faculty member is to gain from this relationship, certain conditions must similarly be present. It is axiomatic that the academician be compatible in philosophy with his executive superior. Similarly important is the need for a well-defined project coupled with a real freedom to explore all avenues for attacking problems. Given these features, the Faculty Residency Program should afford substantial benefits to all involved parties.